How does stigma spoil relationships? Evidence that perceived discrimination harms romantic relationship quality through impaired self‐image. Issue 9 (26th February 2014) - Doyle, David Matthew; Molix, Lisa
Abstract Research is beginning to reveal negative effects of perceived discrimination on romantic relationship quality among members of devalued groups, yet potential mechanisms driving these effects remain underexplored. In the current work, we examined the mediating role of self‐image. Data from two cross‐sectional studies with samples composed of racial minorities (Study 1) and sexual minorities (Study 2) provided support for a model, whereby the negative association between perceived discrimination and romantic relationship quality is partially mediated by impaired self‐image. As proposed, results from bootstrapping analyses revealed significant indirect effects of perceived discrimination on relationship quality through self‐image. Implications of social identity threats for the romantic relationships and families of members of stigmatized groups are discussed along with other potential mechanisms.